UTILIZATION OF ACCOUNTING INFORMATION TO AVOID ESCALATION OF COMMITMENTS ON DECISION MAKING LEVELS WITH LOCUS OF CONTROL AS A MODERATING VARIABLE - Pramesthi, Birgita Nindya (RIMA - Research In Management and Accounting, 2019)
The utilization of information helps an individual accounting for escalation could reduce commitment with the locus of control on which to base these individuals in taking a decision. However, current circumstance when information accounting received unprofitable, then these individuals can do cheating namely escalation commitment. Research aims to scrutinize utilization of information accounting to avoid escalation commitment in levels of decision making with locus of control as moderating variable. Escalation commitment at decision making represented on a scenario cases related to the nature of individual internal locus of control and external locus of control. The experiment was done using by design 2x2x2 between within subjects namely by test student scholarship for Magister Management Catholic Widya Mandala University through instrument cases related to decision making is usually done by manager in companies, by the number of participants 33 people. Experiment is done in class and supervised by researchers. Data from the end of it will analyzed by a statistical means ANOVA. Experimental results show that individual nature locus of external control escalation will hold the act of individual internal commitment than the locus of control. But the nature of individual internal locus of control can reduce the act of escalation commitment if having alternative investment favorable when come using the strategies future benefit in levels of decision making investment.